The Implications of a Tactical Resignation Before the Announcement of a Sanction of Dismissal Mthimkhulu v Standard Bank of SA (2021) 42 ILJ 158 (LC) - Vuyo Peach (Obiter, 2024)
Unlike the typical cases interdicting disciplinary proceedings – which have often not been greeted with judicial applause because of their adverse impact on the Labour Court’s urgent court roll – Mthimkhulu v Standard Bank of SA ((2021) 42 ILJ 158 (LC) (Mthimkhulu)) stands on a slightly different footing. Moshoana J’s instructive decision speaks to the problematic persistence of urgent applications to invalidate unlawful dismissals. The case also replicates a set of fundamental issues concerning the legal effect of post-resignation disciplinary proceedings. In essence, the vexed question is whether an employee who has been found guilty of a serious offence may avoid the ultimate sanction of dismissal by resigning before an employer announces the sanction. To invoke Moshoana J’s colourful language, the applicant’s stance is that “being the first man on the ball, the respondent employer forfeited the right to tackle and play the ball”. Mthimkhulu also invites consideration of jurisdictional quandaries in contemporary labour-dispute resolution regarding the power of the Labour Court to set aside an unlawful dismissal. In a word, the judgment is too good to escape scholarly attention. To respond adequately to the crisp questions arising, the essential starting point remains the pertinent facts at issue in Mthimkhulu. This note conducts an overview of the principles underpinning disposal applications for interim relief. The decision of the Labour Court in the case at hand also affords an opportunity for critical appraisal of all facets of resignation, the instances of the institution and/or continuation of disciplinary proceedings post-resignation, as well as the jurisdictional footprints implicated whenever the Labour Court is asked to invalidate unlawful dismissal.